Trypanotolerant livestock in West and Central Africa. Volume 2. Country studies -Chapter 14. Cameroon - International Livestock Centre for Africa (International Livestock Centre for Africa, 1980)
Data on animal population & distribution; and breed description & body measurements of west African dwarf shorthorn, Bokosi cattle, Muturu cattle, N'Dama cattle, sheep and goats, with a list of research centres and development projects.